2020
DOI: 10.3390/molecules25225451
|View full text |Cite
|
Sign up to set email alerts
|

New Grafted Copolymers Carrying Betaine Units Based on Gellan and N-Vinylimidazole as Precursors for Design of Drug Delivery Systems

Abstract: New grafted copolymers possessing structural units of 1-vinyl-3-(1-carboxymethyl) imidazolium betaine were obtained by graft copolymerization of N-vinylimidazole onto gellan gum followed by the polymer-analogous reactions on grafted polymer with the highest grafting percentage using sodium chloroacetate as the betainization agent. The grafted copolymers were prepared using ammonium persulfate/N,N,N′,N′ tetramethylethylenediamine in a nitrogen atmosphere. The grafting reaction conditions were optimized by chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…A new sustained drug release system based on graft copolymers with a betaine structure has been synthesized from gellan and N-vinylimidazole [121]. Graft copolymers with betaine structure were obtained by a two-step reaction (Figure 5).…”
Section: Other Drug Delivery Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…A new sustained drug release system based on graft copolymers with a betaine structure has been synthesized from gellan and N-vinylimidazole [121]. Graft copolymers with betaine structure were obtained by a two-step reaction (Figure 5).…”
Section: Other Drug Delivery Systemsmentioning
confidence: 99%
“…In vitro cefotaxime sodium salts (CF) release studies demonstrated the ability of the new graft copolymers to immobilize amphoteric drugs. It was also revealed that the mechanism of CF release from PG and PGB1 samples was controlled by the diffusion process or a combination of diffusion and swelling processes [121].…”
Section: Other Drug Delivery Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the choice of macromolecular support for immobilization of bioactive compounds is very important. Encouraged by the preliminary results obtained in our previous study [ 42 ], we chose to use for the immobilization of these new bioactive compounds two types of macromolecular supports: grafted copolymers and grafted copolymers carrying betaine units based on gellan and N-vinylimidazole (PG and PGB1, respectively). The structure of PG and PGB1 copolymers are presented in Figure 1 .…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] Also, its tertiary nitrogen atom can participate in substitution or addition reactions with different betainizing agents, resulting in the preparation of polymers with betaine structure. 12,13 Polybetaines have been distinguished in their biocompatibility, hydrophilicity, antibacterial and antifouling properties. [14][15][16] The great diversity of polybetaines is due to several factors: the type of the anionic groups (carboxylate, sulfonate, or phosphate/phosphinate/phosphonate), the different lengths of the alkyl chain that separates the two ionic groups, and the chemical structure of monomers or polymers used in the synthesis of polybetaines.…”
mentioning
confidence: 99%